Deletion of GABA‐B Receptor in Schwann Cells Regulates Remak Bundles and Small Nociceptive C‐fibers. Issue 4 (29th January 2014) - Faroni, Alessandro; Castelnovo, Luca Franco; Procacci, Patrizia; Caffino, Lucia; Fumagalli, Fabio; Melfi, Simona; Gambarotta, Giovanna; Bettler, Bernhard; Wrabetz, Lawrence; Magnaghi, Valerio
<x xml:space="preserve">Abstract</x> The mechanisms regulating the differentiation into non‐myelinating Schwann cells is not completely understood. Recent evidence indicates that GABA‐B receptors may regulate myelination and nociception in the peripheral nervous system. GABA‐B receptor total knock‐out mice exhibit morphological and molecular changes in peripheral myelin. The number of small myelinated fibers is higher and associated with altered pain sensitivity. Herein, we analyzed whether these changes may be produced by a specific deletion of GABA‐B receptors in Schwann cells. The conditional mice (P0‐GABA‐B1fl/fl) show a morphological phenotype characterized by a peculiar increase in the number of small unmyelinated fibers and Remak bundles, including nociceptive C‐fibers. The P0‐GABA‐B1fl/fl mice are hyperalgesic and allodynic. In these mice, the morphological and behavioral changes are associated with a downregulation of neuregulin 1 expression in nerves. Our findings suggest that the altered pain sensitivity derives from a Schwann cell‐specific loss of GABA‐B receptor functions, pointing to a role for GABA‐B receptors in the regulation of Schwann cell maturation towards the non‐myelinating phenotype. GLIA 2014;62:548–565